Euro Area Policies : Financial Sector Assessment Program-Technical Note-Supervision and Oversight of Central Counterparties and Central Securities Depositories. (IMF Staff Country Reports; Country Report ;, 2018)
Regulation, supervision, and oversight of central counterparties (CCPs) and central securities depositories (CSDs) in the euro area is evolving. Recent proposed amendments to the European Market Infrastructure Regulation (EMIR) are expected to further alter the landscape, as is the European Central Bank (ECB) proposal to amend article 22 of the Statute of the European System of Central Banks (ESCB) and the ECB. The main objective of this note is to analyze the regulatory and supervisory structure applicable to CCPs and International CSDs (ICSDs) in the European Union (EU) and assess their suitability using international standards and good practices.